Pembuatan Biodiesel Dari Minyak Sawit Off -Grade Menggunakan katalis CaO Yang Berasal Dari Kulit Telur Melalui Proses Dua Tahap - Putri, Febrina Dwi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Biodiesel is an alternative the fuel of derived from vegetable oil transesterification reaction with methanol. Off-grade palm is one of the sources of vegetable oils that can be used as raw material for making biodiesel. In the transesterification reaction using a CaO catalyst. CaO obtained from calcined of eggshell at a temperature of 900ÂºC during 2 hours. This goal of research to produce biodiesel from off-grade palm use a two-stage reaction, study the performance of the CaO catalyst calcined of eggshell on the transesterification reaction, and determine the reaction of temperature influence, mole ratio of oil:methanol, and the concentration of catalyst on the yield of biodiesel transesterification reaction. Esterification is runned at a temperature of 60Â°C with a mole ratio of oil:methanol 1:12 and use1%wt of catalyst H2SO4. FFA can be lowered from 16.18% to 0.6%. Transesterification conducted with variations mole ratio of oil:methanol 1:7, 1:9, 1:11, catalyst of CaO concentrations are 2%wt, 4%wt, 6%wt, 50ÂºC, 60ÂºC, 70ÂºC of temperatureâs reaction and reaction time during 2 hours. Processing of the data conducted by Response Surface Methodology (RSM), while the number of experiments are determined by Central Composite Design (CCD). Yield is resulted in this research are 62.30%-87.41%. Optimums yield is produced at a temperature of 70ÂºC with a mole ratio of oil:methanol 1:11 and catalyst of CaO 2%wt. Process conditions which significant effect on the yield of biodiesel are the reaction temperature, mole ratio of oil:methanol, and the interaction between temperature with mole ratio of oil:methanol but in the other side, the catalyst concentration does not have a significant influence.Keywords: biodiesel, CaO, off-grade palm oil, rsm, transesterification